Petroglyphs and reliefs in temples, convents and Casonas del Cusco - Zecenarro Benavente, Germán (2007)
In some edifications lifted up starting from the XVI Century, there are ancient stones that show on their surfaces enigmatic incisions, elements that belong to the religious and ritual Andean World. There are many important traces of these cultural expressions in Cusco than, by their relation with particular urban spaces, some architectonic typologies from the Virreinato or Inka's antique sacred contexts, can attach them magician and religious contents. This fact confirms the continuity of the sacred entities of the Andes in the established occidental architecture.